Intralabyrinthine Schwannomas: Imaging Diagnosis and Classification - Salzman, K.L. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: ILS is a rare lesion that has a different management from the more common “acoustic” schwannoma. To date, only 137 cases have been reported. We present a classification scheme based on labyrinthine anatomy to describe and localize these lesions. Treatment and prognosis hinge on the appropriate localization of these tumors; thus, a concise terminology that can be used by both the otolaryngologist and radiology communities is desirable. MATERIALS AND METHODS: After approval of the institutional review board, a retrospective study of all patients with the diagnosis of ILS imaged between 1996 and 2010 was performed. Clinical and imaging data were collected. Patients were imaged with thin-section high-resolution T2 and contrast-enhanced MR imaging. RESULTS: There were 45 patients with a diagnosis of ILS. Forty-three had complete histories. There were 18 male and 25 female patients with an age range of 21–78 years with a mean age of 53 years. The most common presenting symptom was progressive sensorineural hearing loss. Lesions were characterized on the basis of their location. Intracochlear was most common (14/45) followed by transmodiolar (13/45), intravestibular (7/45), vestibulocochlear (5/45), transmacular (4/45), and transotic (2/45). Sixteen patients underwent surgical resection. The remaining patients were followed clinically and by serial MR imaging. CONCLUSIONS: ILS is an uncommon but under-reported tumor. We characterized the MR imaging appearance of these tumors by using high-resolution techniques. In addition, an anatomically based classification system is presented that will help the radiologist accurately describe ILS within the inner ear and help the surgeon determine which tumors are potential surgical candidates.